2000
DOI: 10.1094/phyto.2000.90.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bactericides on Population Sizes and Spread of Clavibacter michiganensis subsp. michiganensis on Tomatoes in the Greenhouse and on Disease Development and Crop Yield in the Field

Abstract: Chemical applications, with the exception of mancozeb, reduced population sizes and spread of Clavibacter michiganensis subsp. michiganensis among tomato seedlings in the greenhouse and impacted subsequent plant development and yield in the field. While applications of copper hydroxide, copper hydroxide/mancozeb, copper hydroxide/mancozeb (premixed 12 h before spraying), streptomycin, and streptomycin/copper hydroxide to seedlings in the greenhouse did not differ significantly from the inoculated control, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Products containing copper has reported to significantly reduce foliar leaf, fruit spotting produced by this pathogen (Gleason et al, 1993). Copper treatments were more active when mixed with mancozeb, suggesting a synergistic effect because mancozeb alone did not reduce populations or spread (Hausbeck et al, 2000). Such enhanced activity has also been reported on Pseudomonas syringae pv.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Products containing copper has reported to significantly reduce foliar leaf, fruit spotting produced by this pathogen (Gleason et al, 1993). Copper treatments were more active when mixed with mancozeb, suggesting a synergistic effect because mancozeb alone did not reduce populations or spread (Hausbeck et al, 2000). Such enhanced activity has also been reported on Pseudomonas syringae pv.…”
Section: Discussionmentioning
confidence: 76%
“…By contrast, streptocycline did reduce leaf symptoms produced by spray inoculation in two independent trials, and the black spots on the leaves and stems in one. Bacillus subtilis were considerably reduced in the field by the application of the antagonist (Okigbo and Osuinde, 2003), differences in disease control according to the inoculation method (Hausbeck et al 2000) reported that streptomycin applied to seedlings inoculated by misting increased their survival after transplant and prevented severe disease symptoms from developing in the field, Streptocycline was best chemical for control (Mishra and Prakash, 1992). In our study, streptomycin was used as a positive control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting example is the combination of cuprocalcic sulfate plus mancozeb because it has a synergistic effect against several bacterial diseases (Hausbeck et al, 2000;Jones et al, 1991;Marco & Stall, 1983). Currently copper oxychloride is the copper compound most commonly recommended against olive knot disease by the Spanish extension services.…”
Section: Direct Controlmentioning
confidence: 99%
“…Both strains had been previously characterized by Rep-PCR and belong to the A and C DNA fingerprint classes, respectively (Francis et al 2001;Louws et al 1998). A loop full of Cmm A226 and C290 cells was transferred to two separate flasks containing 5 ml of nutrient broth yeast extract without glucose (NBY; Hausbeck et al 2000;Schaad 1980) and incubated at 25C, 250 rpm, for 48 h. Each 5-ml culture was then inoculated into 1 l of NBY and incubated at 25C, 250 rpm, for 24 h. The cells were pelleted at 10,000 rpm, 4C, for 10 min, resuspended once in ddH 2 O, centrifuged at 10,000 rpm, 4C, for 10 min, and the remaining pellet resuspended in 25 ml ddH 2 O. The bacterial concentrations were estimated by measuring the transmittance of a 1:4 dilution using a Beckman DU 640 spectrophotometer.…”
Section: Inoculum Preparation and Disease Evaluationmentioning
confidence: 99%